Pasture production–diversity relationships in a kānuka silvopastoral system - Mackay-Smith TH; López IF; Burkitt LL; Reid JI (John Wiley & Sons Ltd on behalf of British Ecological Society, 2023)
Silvopastoral systems have great potential for forming multifunctional landscapes that provide a range of economic and environmental benefits to pastoral land. However, pasture production–diversity relationships in silvopastures require further exploration. This study measures how pasture functional group production, pasture species diversity and pasture functional diversity (FD) are impacted by trees in a novel native silvopastoral system in New Zealand hill country with kānuka (Kunzea spp.). Silvopastoral trees facilitated the growth of fast-growing competitor functional groups (Lolium perenne, Dactylis glomerata and high fertility annuals: Bromus hordeaceus and Critesion murinum), because of positive impacts on soil fertility, organic matter and porosity. Shannon diversity, species richness and species evenness were significantly less in the more productive pastoral environment under the trees, but functional richness, functional evenness and functional dispersion were similar between kānuka pasture and open pasture. These results show that silvopastures can increase pasture production by promoting the growth of competitive pasture functional groups, and that reduced species diversity under silvopastoral trees does not necessarily impact FD in the context of production. Moreover, species indices overestimated diversity reductions under the trees compared to functional indices. Thus, considering FD in silvopastoral systems is integral for not misinterpreting diversity outcomes.
Keywords: agroforestry; alpha diversity; biodiversity; botanical composition; kanuka; mass ratio hypothesis; pasture stability; poplar silvopastures; tree-pasture